Analysis of the Effectiveness of Marketing 4.0 Approaches and Customer Path Models to Increase Clinical Visits - Jannah, Rohilatul; Soliha, Soliha; Haniwijaya Tjokro, Silvia (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
The development between hospitals in the digital era is getting more advanced day by day. Marketing 4.0 can be used as a method to increase clinic visits in hospitals. The study aims to analyze efforts to increase clinic visits through marketing 4.0 and analysis of of the effectiveness of Marketing 4.0 approaches and Customer Path Models to increase clinical visits. The cross-sectional analytic study was conducted in a single private hospital institution in East Java, Indonesia in pediatric health clinics, integrated services, and an effective hospital reach of 2 kilometers. 175 respondents consisting of 97.7% of respondents who know about child health clinics and/or integrated services, 87.7% of respondents who are interested in using these two services, 90.7% of respondents who seek information about these two services, and 90.7 % of respondents who use the child health clinic and/or integrated services by 74.3%. The results of in-depth interviews and focus group discussions with hos-pital leaders found that the use of social media was not maximal, the number of insurance companies that joined the hospital was not enough, a special community for children with special needs had not been formed, there were no mobile phone applications and online registration systems, and the system had not yet been integrated. comprehensive hospital management information. The customer path in both services is a funnel pattern, so the hospital must increase its commitment and affinity through omni-channel marketing, mobile application establishment, social CRM, and gamification.